2005
DOI: 10.1128/jcm.43.5.2497-2499.2005
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin-Resistant Group A Streptococcal Isolates Collected between 2000 and 2005 in Oahu, Hawaii, and Their emm Types

Abstract: We examined erythromycin and clindamycin susceptibilities with Etest methodology among 546 group A streptococcal isolates collected in Hawaii between February 2000 and November 2004. Erythromycin resistance was low (3.1%). No isolate was clindamycin resistant. The prevalence of erythromycin resistance in group A streptococci remains low in Hawaii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…In the year 2003, the study conducted at our laboratory showed predominance of emm 81 type in North Indian community, which has also been reported from other countries [8,16,18,19,20]. Report of association of emm 81 with invasive disease in Sweden and Romania [17,20] prompted us to look for a virulent potential of the circulating predominant emm 81 isolates from our community.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the year 2003, the study conducted at our laboratory showed predominance of emm 81 type in North Indian community, which has also been reported from other countries [8,16,18,19,20]. Report of association of emm 81 with invasive disease in Sweden and Romania [17,20] prompted us to look for a virulent potential of the circulating predominant emm 81 isolates from our community.…”
Section: Discussionsupporting
confidence: 74%
“…No penicillin resistant isolate have ever been reported from any region of world in spite of its extensive and indiscriminate usage [7] and our results also showed susceptibility of all emm81 strains to penicillin. As regards macrolides, insight into Indian literature till 2002 indicated less than 1% erythromycin resistance rates among GAS which increased to 9.04% in 2006 [9], while the present study indicated 50% resistance among emm 81 isolates, comparable to the reports of increasing resistance from other countries of the world [8,19]. A new macrolide azithromycin being used extensively in the country for past few years alongwith co-trimaxazole also exhibited high resistance among isolates.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In recurrent infections, clindamycin and amoxicillin-clavulanate are used to prevent infection (Bisno & Kaplan, 2002). GAS have developed resistance to sulfonamides, tetracycline and erythromycin worldwide, which is attributed to their increased prescription (Capoor et al, 2006;Erdem et al, 2005). However, the rationale is that GAS still remain uniformly susceptible to penicillin in spite of well-documented penicillin resistance in other Gram-positive, closely related species, such as Streptococcus pneumoniae, viridans streptococci and Enterococcus species.…”
Section: Introductionmentioning
confidence: 99%
“…The erythromycin resistance rate (ϳ3%) has been low among group A streptococcus (GAS) isolates in Hawaii, where impetigo, acute rheumatic fever, and clusters of necrotizing fasciitis have been reported (5)(6)(7)(8)(9)(10); G. Erdem, G. Matsuura, G. Wheelen, C. Mizumoto, D. Esaki, and P. V. Effler, presented at the XVIIth Lancefield International Symposium on Streptococci and Streptococcal Diseases, Porto Heli, Greece, 2008). During a retrospective survey of 250 GAS cultures collected from patients with invasive GAS disease identified between the years 2005 and 2007, the reviews of the clinical information incidentally showed erythromycin and clindamycin resistance in five patients.…”
mentioning
confidence: 99%